Caracterización fenotípica del cerdo criollo en los cantones Zapotillo y Puyango de la provincia de Loja - Espinosa Pullaguari, Jimmy Danilo (2016)
A phenotypical characterization of the Creole pig was conducted in the Zapotillo and Puyango cantons of the province of Loja, during 2015-2016. Throughout the field work data collection was conducted using the non-probability snowball method on a selection of 34 Creole pigs, aged one year or more and both sexes and recorded on a registration form. Measurements were made using a zoometric cane, drill compass, measuring tape and digital scales. Phenotypic characterization included 17 zoometric measures 9 zoometric indices and 7 phanaeroptical characteristics. The main indicators of the variable zoometric measures with their respective averages for both cantons were: body weight (BW) 53.24; head length (HL) 31.01; head width (HW) 13.59; snout length (SL) 15.10; snout width (SW) 8.54; rump length (RL) 25.61; rump width (RW) 18.37; bicostal diameter (BCD) 20.76; diameter ; back ribs diameter (BRD) 31.73; withers height (WH) 60.95; rump height (RH) 66.00; height at the root of the tail (HRT) 49.89; longitudinal diameter (LD) 79.81; chest perimeter (CHP) 92.70; cannon bone perimeter (CBP) 14.64; ear length (EL) 20.27; and ear width (EW) 15.63.